A Constraints Driven Product Lifecycle Management Framework - Le Duigou, Julien; Bernard, Alain; Perry, Nicolas; Delplace, Jean-Charles (Cranfield University Press, 2009)
The management of the product information during its lifecycle is a strategic issue for the industry. In this paper, a constraints driven framework is proposed to create and manage the product information. The method proposes to each actor that intervenes on the product life cycle to act on the quote, the development or the industrialisation of the product. From each phase of the product lifecycle, the extraction, capitalisation and reuse of fundamental knowledge is coordinated by a generic meta-model. This paper explains this approach through experiments in three different SMEs of the mechanical industry.
Organised by: Cranfield University
Keywords: Product Lifecycle Management; Knowledge Based Engineering; Information System